MMF linac high energy part LLRF system status - Sharamentov, S.I.; Edachev, V.V.; Kuznetsov, V.V.; Peplov, V.V. (Вопросы атомной науки и техники, 1999)
Accelerated beam quality and level of beam losses are strongly affected by accelerating field phase and amplitude stability and accuracy. Due to this a constant attention was paid to the Low Level RF systems of the MMF linac. During the last 4-5 years many components of LLRF system of high -energy part of MMF linac were significantly rebuilt and reconstructed, and as a result higher accuracy and longterm stability were achieved, along with the higher reliability and more simple maintenance. Besides, the time needed to carry out a procedure of linac accelerating cavities, longitudinal tuning (setting and adjusting of nominal values of amplitudes and phases in the accelerating cavities), was reasonably decreased. Also, a preamplifier feeding the input of the klystron amplifier was modified to get more reliable operation.